2019
DOI: 10.1016/j.heliyon.2019.e02349
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary survey of extended-spectrum β-lactamases (ESBLs) in nosocomial uropathogen Klebsiella pneumoniae in north-central Iran

Abstract: Infections caused by extended-spectrum β-lactamases (ESBLs) producing bacteria, including Klebsiella pneumoniae have increasingly subjected to therapeutic limitations and patients with these infections are at high risk for treatment failure, long hospital stays, high health care costs, and high mortality. The aim of this study was to screen the prevalence of the blaTEM,blaCTX-M and blaSHV ESBL genes in K. pneumoniae strains isolated from nosocomial urinary tract infections (UTIs). During the March 2016 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
7
22
0
Order By: Relevance
“…So far, similar to our findings, several studies have reported the co-existence of ESBL genes in Enterobacteriaceae. 34,36,37…”
Section: Discussionmentioning
confidence: 99%
“…So far, similar to our findings, several studies have reported the co-existence of ESBL genes in Enterobacteriaceae. 34,36,37…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistant (MDR) organism, by definition, is a germ that is resistant to more than three classes of antibiotics [ 14 ]. A review of literature shows that there is an increase in extended spectrum beta-lactamase (ESBL)-producing MDR organisms among both CAUTIs and HAUTIs, threatening the public health sector as a whole [ 15 ]. Infections caused by MDR organisms are associated with longer hospital stay and increased financial burden [ 16 ], not to mention poorer patient outcomes, delayed symptoms resolution, and advanced disease progression in case of ascending infections [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huai et al [19] reported Klebsiella pneumoniae isolates that had high rate of resistance to impenem in China. Similarly, Yazdansetad et al [20] a 50% rate of extended spectrum β-lactamase (ESBL) producing K. pneumoniae in Iran. In this study Klebsiella spp.…”
Section: Discussionmentioning
confidence: 98%